OsPRMT6b balances plant growth and high temperature stress by feedback inhibition of abscisic acid signaling - Xin Jin; Qibing Lin; Xinyue Zhang; Shuang Zhang; Weiwei Ma; Peike Sheng; Limin Zhang; Minxi Wu; Xudong Zhu; Zhiwei Li; Bojuan Liu; Jiachang Wang; et al. (Nature Communications)
Abstract Plants rapidly induce strong abscisic acid (ABA) signaling in response to stress, but how they weaken ABA signaling to resume normal growth after stress is unclear. Here, we find that arginine methyltransferase 6b (OsPRMT6b) methylates three arginine residues (R48, R79, R113) in ABA receptor OsPYL/RCAR10 (OsPYR1-LIKE/REGULATORY COMPONENT OF ABA RECEPTOR, R10), thereby enhancing its interaction with Tiller Enhancer (TE) and promoting its ubiquitination and degradation through the 26S-proteasome pathway. OsPRMT6b is induced by ABA at both transcriptional and translational levels. Further, we find that R10 protein accumulates under high temperature stress but declines as temperature drops, whereas OsPRMT6b protein shows an opposite trend. And WT plants display a better growth recovery than osprmt6b mutants after high temperature. These findings suggest that OsPRMT6b acts as a switch to downregulate ABA signaling for growth recovery after high temperature stress.